PARTISIPASI ANAK DALAM BERNYANYI TERHADAP PENGEMBANGAN KEMAMPUAN BERBAHASA ARAB - Elmi - Hidayana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This research aims to discover how children's participation in the singing method develops Arabic language skills and how the influence of children in the singing method of Arabic language skills. This study uses a quantitative approach with the object of research in class VIII B MTSN 3 Ponorogo. Data collection uses observation, test, and documentation techniques. The analysis technique uses the percentage and correlation of product moments. From the results of data analysis, it can be concluded that (1) child participation while learning Arabic using the singing learning method in class VIII B MTsN 3 Ponorogo is quite good with a percentage of 69 %, (2) Arabic language skills Children through singing learning methods implemented In class VIII B MTsN 3 Ponorogo is quite good, with a percentage of 70, 4 %, and (3) there is an influence on children in the singing method on the ability to speak Arabic children in MTsN 3 Ponorogo 0.935